Analisis Kualitas Kinerja Karyawan Pada Bank Mayapada Cabang Darmo 57 Surabaya - Permana, I Gede Wisnu Angga (widya balina, 2025)
The performance of Mayapada Bank employees at Darmo 57 Surabaya Branch can be assessed from their ability to complete tasks well and on time. This good performance is very important for the success of the company. However, several factors such as lack of motivation, low discipline, negative work environment influences, and lack of role models can hinder employee performance. At this time, Mayapada Bank Darmo 57 Branch finds it difficult to build and improve employee performance, therefore employee performance must be improved to improve the quality of employee work. The data analysis technique needed is data reduction (data reduction) reducing data means summarizing and data display (data presentation) limiting a presentation as a set of structured information that allows for drawing conclusions and taking action. Source triangulation to test data credibility is done by checking the data that has been obtained. Technique triangulation to test data credibility is done by checking data to the same source with different techniques. Time triangulation often affects data credibility. Based on the results of interviews conducted by researchers, several factors emerged that influenced the quality of employee performance, namely a Comfortable Work Environment, Leadership Style, Salary, Routine Meetings.